The Importance of the Role of Parents in Ability Toilet Training for Pre-School Children - Septy Ariani; Evi Rufaida (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Pre-school age children have not been able to take care of themselves such as wearing clothes, bathing, eating, using the toilet and so on. Parents have an active role in preschool children about toilet training by training their children's ability to urinate and defecate to the toilet. the purpose of organizing this service activity is to provide knowledge and understanding to parents about the importance of toilet training for pre-school children. The method used is counseling. The target of this service is parents who have pre-school age children reaching 20 people. The stages applied in the implementation of this activity are preparation, implementation, and evaluation of service activities. Based on the results of the activity evaluation, it was found that parents felt the benefits of this service activity and they had knowledge and understanding of how and the importance of the role of parents in toilet training abilities in children. It can be said that this service activity is able to equip parents in accompanying their children during the pre-school period, especially regarding toilet training.